More than movement: a systematic review of moral and social development in adolescents physical education - Magdalena Jadwiszczak; Sara Wawrzyniak; Krzysztof Pezdek (BMC Public Health)
Abstract Background This paper investigates the dimensions of moral and social development within physical education (PE) programs for adolescents, examining theoretical foundations, empirical evidence, and practical implementations. The review highlights the role of PE in fostering moral and social development and explores how cultural contexts may influence research and practice. By integrating these dimensions, the study provides a comprehensive understanding of how PE contributes to adolescent development while accounting for cultural variability. Methods A systematic review was conducted using Web of Science, EBSCO, and Scopus databases. The final search was performed in July 2024. A total of 3,114 non-duplicate articles were identified. After screening titles, abstracts, and full texts, 44 studies met the inclusion criteria. Studies were assessed based on methodologies, program structures, findings, and alignment with cultural values. Results The review indicates that PE programs integrating moral education contribute to the development of students’ moral and social competencies. Programs appeared to be designed that align with prevailing cultural values and traditions, which may enhance their perceived relevance and acceptance. However, due to the methodological diversity of included studies, direct comparisons across studies were limited. Conclusions The findings suggest that PE-based programs promoting moral and social development are generally effective. Further research, including meta-analyses, is recommended to compare different program approaches systematically. Future studies should also aim to standardize evaluation methods to improve comparability and explicitly consider cultural context as an important factor influencing program design and outcomes.